The outlook for Azerbaijani gas supplies to Europe : challenges and perspectives - Rzayeva, G (Oxford Institute for Energy Studies, 2015)
As the birthplace of the oil and gas industry, Azerbaijan’s long and rich history is intertwined with hydrocarbon production, with oil drilling pre-dating activity in Pennsylvania by 13 years. The involvement of foreign oil companies in the late 1800s, including the Nobel Brothers, resulted in the country becoming the world’s foremost oil producer at the turn of that century. The Soviet era precluded further international investment, but saw a dramatic growth in gas production commencing in the 1920s. The 1990s witnessed the return of the IOCs with the Azeri-Chirag-Guneshli field (oil and associated gas) and the Shah Deniz (gas and condensate) field developments reversing the trend of production decline and creating an export surplus in both oil and gas. In this paper, Gulmira Rzayeva provides a comprehensive analysis of the challenges which were surmounted in the development of the Shah Deniz field, not least of which related to establishing export pipelines and marketing arrangements in Turkey, and (for Phase 2) Europe. Turning to the future, the paper details the nature and estimated potential of partially developed fields, discoveries at varying stages of appraisal and prospective structures in the Azerbaijan sector of the Caspian Sea. Apart from the inevitable range of uncertainty over future production levels and timing, what emerges are the twin challenges of drilling rig availability (it being impossible to bring an assembled rig into the Caspian due to width restrictions on the Volga-Don canal) and the highly challenging sub-surface drilling conditions. The modest prospects for domestic gas demand growth and Azerbaijan’s geographic location require that any future gas field development decision will also require a degree of certainty on export infrastructure capacity to the primary target markets of Turkey and South and South East Europe. These issues are covered in detail.